2022
DOI: 10.1016/j.ymeth.2022.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven case fatality rate estimation for the primary lineage of SARS-CoV-2 in Poland

Abstract: After more than one and a half year since the COVID-19 pandemics outbreak the scientific world is constantly trying to understand its dynamics. In this paper of the case fatality rates (CFR) for COVID-19 we study the historic data regarding mortality in Poland during the first six months of pandemic, when no SARS-CoV-2 variants of concern were present among infected. To this end, we apply competing risk models to perform both uni- and multivariate analyses on specific subpopulations selected by different facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Overall mortality reported in our analysis (6 out of 173 patients, 3.47%) is consistent with the results of the large meta-analysis, where 1416 out of 41,113 (3.44%) HIV–SARS-CoV-2-coinfected individuals died [ 21 ] and slightly lower than the overall case-fatality ratio of 5.43% estimated by a large Polish study conducted in the first months of pandemic, before the first variants of concern were identified [ 22 ].…”
Section: Discussionsupporting
confidence: 88%
“…Overall mortality reported in our analysis (6 out of 173 patients, 3.47%) is consistent with the results of the large meta-analysis, where 1416 out of 41,113 (3.44%) HIV–SARS-CoV-2-coinfected individuals died [ 21 ] and slightly lower than the overall case-fatality ratio of 5.43% estimated by a large Polish study conducted in the first months of pandemic, before the first variants of concern were identified [ 22 ].…”
Section: Discussionsupporting
confidence: 88%
“…Mutation points as single nucleotide polymorphisms (SNPs) are identified in each virus clade detected through this phylogenetic analysis. These global dataset analyses further reveal that climatic and socio-demographic conditions have a more significant role in the spread of COVID-19, highlighted in the following works of Chatterjee et al [2] and Gogolewski et al [3] . In the work of Chatterjee et al [2] , the relationship of socio-demographic conditions, such as temperature, humidity, and population density of the regions, with the region-specific outbreak intensity of COVID-19 has been identified by the application of fuzzy association rule mining on COVID and social data collected from different countries.…”
mentioning
confidence: 76%
“…In the work of Chatterjee et al [2] , the relationship of socio-demographic conditions, such as temperature, humidity, and population density of the regions, with the region-specific outbreak intensity of COVID-19 has been identified by the application of fuzzy association rule mining on COVID and social data collected from different countries. While in the work of Gogolewski et al [3] , case fatality rates (CFR) for COVID-19 have been extensively studied based on the historical data regarding mortality in Poland during the first six months of the pandemic, when no SARS-CoV-2 variants of concern were present among infected. It leads to the CFR's exploration to find its decreasing trend in time.…”
mentioning
confidence: 99%
“…There are only few publications tracing SARS-CoV-2 variants in Poland [ 29 , 34 , 35 , 36 , 37 ]. Most of them based on analysis of viral genomic data deposited at the Global Initiative on Sharing All Influenza Data (GISAID) [ 5 ]; it currently contains 83,764 sequences from Poland [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first VOC, Alpha variant, was identified in a sample collected in October 2020. Interestingly, previous data reported that this variant appeared in Poland in December 2020 [ 37 , 42 ]. Since its emergence, the Alpha variant has gradually increased its proportion in the following months, as we already observed in our previous survey [ 29 ].…”
Section: Discussionmentioning
confidence: 99%